1980
DOI: 10.1093/schbul/6.4.606
|View full text |Cite
|
Sign up to set email alerts
|

Catamnestic Long-term Study on the Course of Life and Aging of Schizophrenics

Abstract: The author summarizes a monograph study on the course of schizophrenia into old age, which he co-authored with C. Müller, and which includes mortality and cause-of-death statistics on 1,642 original cases and an average of 37 years of catamnestic observation of the 289 patients who survived until the final followup examination. The separate investigations of the development of schizophrenia, the psycho-organic symptomatology, and the social adaptability show that the long-term course was favorable in at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
204
3
12

Year Published

1984
1984
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(238 citation statements)
references
References 21 publications
(11 reference statements)
19
204
3
12
Order By: Relevance
“…10,15,19,21,27,[31][32][33][34][35] Our study highlights the importance of suicide prevention, not only during the early years but also later in the course of the illness.…”
Section: Resultsmentioning
confidence: 86%
“…10,15,19,21,27,[31][32][33][34][35] Our study highlights the importance of suicide prevention, not only during the early years but also later in the course of the illness.…”
Section: Resultsmentioning
confidence: 86%
“…Another possibility could be that the processes of aging and the possibility of psychopathological improvement during the later stages of schizophrenia (Bleuler, 1978;Ciompi, 1980;Harding et al, 1987;Mason et al, 1995) "neutralize" each other, producing effectively unchanged performance across this age span. The clinical measures used in this study (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…18 Strauss and Carpenter 19 evaluated the progression of schizophrenia over time and found that most symptoms improve in 20% of patients, remain unchanged in 60%, and worsen in only 20% of patients. Ciompi 20 suggested that advancing age might mitigate the intensity of schizophrenic illness, allowing more patients to live as outpatients with residual states.…”
Section: Schizophreniamentioning
confidence: 99%